Pomegranate Extract Administration Reverses Loss of Motor Coordination and Prevents Oxidative Stress in Cerebellum of Aging Mice - David Verdú; Alicia Valls; Ana Díaz; Aitor Carretero; Mar Dromant; Julia Kuligowski; Eva Serna; José Viña (MDPI AG, 2023)
The cerebellum is responsible for complex motor functions, like maintaining balance and stance, coordination of voluntary movements, motor learning, and cognitive tasks. During aging, most of these functions deteriorate, which results in falls and accidents. The aim of this work was to elucidate the effect of a standardized pomegranate extract during four months of supplementation in elderly mice to prevent frailty and improve the oxidative state. Male C57Bl/6J eighteen-month-old mice were evaluated for frailty using the "Valencia Score" at pre-supplementation and post-supplementation periods. We analyzed lipid peroxidation in the cerebellum and brain cortex and the glutathione redox status in peripheral blood. In addition, a set of aging-related genes in cerebellum and apoptosis biomarkers was measured via real-time polymerase chain reaction (RT-PCR). Our results showed that pomegranate extract supplementation improved the motor skills of C57Bl/6J aged mice in motor coordination, neuromuscular function, and monthly weight loss, but no changes in grip strength and endurance were found. Furthermore, pomegranate extract reversed the increase in malondialdehyde due to aging in the cerebellum and increased the reduced glutathione/oxidized glutathione (GSH/GSSG) ratio in the blood. Finally, aging and apoptosis biomarkers improved in aged mice supplemented with pomegranate extract in the cerebellum but not in the cerebral cortex.